2013
DOI: 10.1186/1471-2296-14-21
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pulmonary rehabilitation in patients with moderate chronic obstructive pulmonary disease: a randomized controlled trial

Abstract: BackgroundPulmonary Rehabilitation for moderate Chronic Obstructive Pulmonary Disease in primary care could improve patients’ quality of life.MethodsThis study aimed to assess the efficacy of a 3-month Pulmonary Rehabilitation (PR) program with a further 9 months of maintenance (RHBM group) compared with both PR for 3 months without further maintenance (RHB group) and usual care in improving the quality of life of patients with moderate COPD.We conducted a parallel-group, randomized clinical trial in Majorca p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 39 publications
4
73
2
3
Order By: Relevance
“…Of these, 58 were considered potentially relevant and 23 studies 17,18,19,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50 met the eligibility criteria and were included in this review. One of the selected studies appeared in two distinct publications 49,50 in which the same intervention was applied to the same patients but describing different outcomes.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 58 were considered potentially relevant and 23 studies 17,18,19,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50 met the eligibility criteria and were included in this review. One of the selected studies appeared in two distinct publications 49,50 in which the same intervention was applied to the same patients but describing different outcomes.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Thirteen studies were done in Europe 17,19,21,31,33,38,42,43,45,46,48,49,50 , six in Asia 30,36,39,40,44,47 , two in Australasia 34,35 , one in North America 41 , and one in South America 32 . Among the studies included in the review, 19 17,18,19,30,31,32,33,34,36,38,39,40,42,43,44,46,47,48,49,50 compared HCPR to control group (n = total 893; n HCPR = 485), while four 35,37,41,45 compared HCPR to OPR (n total = 375; n HCPR = 178). No studies reported harmful effects related to HCPR during interventions.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…В объединенном анализе данных больных (n = 623) из 9 исследований [82][83][84][85][86][87][88][89][90] легочная реа билитация привела к существенному снижению час тоты госпитализаций по сравнению с обычным лечением (ОШ -0,45; 95% ный ДИ -0,22-0,91; р = 0,03). В целом качество этих доказательств оце нено как низкое или очень низкое из за риска систе матических ошибок, нестабильности и неточности результатов.…”
Section: клинические рекомендацииunclassified